Analysis of Foreign Aid-Induced Investigative Journalism Practice in Nigeria (Journal of Management and Social Sciences, 2019)
This study was conducted to analyse foreign aid-induced investigative journalism practice in Nigeria. It used quantitative approaches that combined content and document analyses. Published investigative stories from journalists trained from the independent media extractions that benefited from media development assistance in 2014 and 2017 constitute the study population. Purposive sampling procedure was used to select samples from the population and content categories and rubric scale were the instruments of data collection. The study revealed the gains and consequences of international media development assistance on investigative journalism practice in Nigeria and recommendations are suggested to the concerned stakeholders based on the conclusion.